Public sector opinions and foresight towards Rail Baltica alignment : in search of growth seeds - Laisi, Milla; Henttu, Ville; Panova, Yulia; Karamysheva, Marina; Hilmola, Olli-Pekka; Lappeenrannan teknillinen yliopisto. Tuotantotalouden tiedekunta. LUT Kouvola (LUT Scientific and Expertise publications, ISSN 2243-3376, 2013)
Abstract.
Keywords: Transportation; Railroads; Interviews; Delphi method; kuljetus; raideliikenne; rautatieliikenne; haastattelututkimus; kyselytutkimus; tutkimushaastattelut; julkinen sektori; delfoimenetelmä; Russia; Europe; Baltic States; Venäjä; Eurooppa; Baltia